The Orientation Towards Helping Others and its Relationship with Emotional Awareness among University Students - Shaaban, Hanan Hussein Ibrahim; Al-Shawareb, Iyad Grace (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identifythe orientation towards helping others and its relationship with emotional awareness among haifa university students. The sample of the study consisted of (540) male and female from haifa university in palestinein Palestine during the academic year 2020/2021. to achieve the aim of the study, the researcher developed the orientation towards helping others scale, and emotional awareness scale. Validity and reliability for both scales were obtained. The results showed a high level of orientation towards helping others and emotional awareness among haifa university students, and moderate level of emotional awareness among haifa university students The results also showed that there were no statistically significant differences in the orientation towards helping others and emotional awareness due to the variables of gender and specialization. The results also showed a positive, statistically significant correlation between the orientation towards helping others and the emotional awareness among haifa university students. Several recommendations and suggestions were provided; including conducting a study that examines the relationship between the tendency towards helping others and emotional awareness on other segments of students, and in different environments in Palestinian society, and comparing its results with the results of the current study.